Different Prevalence of Chronic-Non-Infectious Diseases - AM El-Tawil (Tehran University of Medical Sciences, 2010)
"nInflammatory bowel disease, coronary artery disease, cerebrovascular disease, hypertension, diabetes, tumours, are examples of chronic degenerative diseases that have a high prevalence in developed nations. These chronic-non-communicable diseases have multifactorial aetiologies that considered to be caused by the interaction of environmental risk factors with multiple predisposing genes. Genetic researches on these diseases have traditionally focused on investigation aimed at identifying disease-susceptibility genes. Recent evidence suggests that somatically acquired DNA mutations may also contribute significantly to the pathogenesis of these disease states such as coronary artery disease indicating a similarity between the atherosclerotic and carcinogenic processes. The high incidences and prevalence of these chronic diseases in the Western World in comparison with the East and changing trends in disease incidence (seen in many countries) provide strong evidence that those environmental factors as playing a major influence in disease- expression. There is an ample reason to believe that environmental factors have contributed to inducing alterations in genetic code in precedent generations, which were subsequently inherited and further modified by modern life style   activities. Consequently, we now see the appearance of chronic degenerative diseases and their higher incidences in the Western nations   as compared with the Eastern ones.